Sarcoidal granulomas in the spleen associated with multiple carcinomas - Kurata, A.; Takayama, N.; Terado, et al., Y. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2010)
Sarcoid reactions are relatively rare manifestations of epithelioid cell granulomas associated with malignancy; they are especially found in the lymph nodes draining malignant tumors, but rarely found in other organs.We present a case of a 60-year-old female with sarcoid reactions in the spleen identified during the consecutive diagnosis and management of ovarian, breast, and thyroid carcinomas during a period of about 2 years. The symptoms and laboratory data suggestive of systemic sarcoidosis were absent except for a slight mediastinal lymphadenopathy detected only by a computed tomographic scan. The splenic granulomas were accompanied by dendritic cells of mature and immature types, the latter being different from the reported nodal counterparts. To our knowledge, this is the first reported case of splenic sarcoid reactions associated with multiple cancers, and the first reported immunohistochemical detection of dendritic cells in splenic granuloma.